2022
DOI: 10.1002/cncr.34407
|View full text |Cite
|
Sign up to set email alerts
|

Risk of prostate cancer and death after benign transurethral resection of the prostate—A 20‐year population‐based analysis

Abstract: BACKGROUND:The oncological risks after benign histology on a transurethral resection of the prostate (TURP) remain largely unknown.Here, the risk of prostate cancer incidence and mortality following a benign histological assessment of TURP is investigated in a populationbased setting. METHODS: Between 1995 and 2016, 64,059 men in Denmark underwent TURP without prior biopsy of the prostate; 42,558 of these men had benign histology. The risks of prostate cancer, prostate cancer with a Gleason score ≥ 3 + 4, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, direct TURP for diagnostic purposes is not recommended in patients with suspected PC who have not been screened by biopsy [1,4]. Although it was not recommended, our results, actual clinical practice, and literature report all found that many suspected PC patients were still directly undergoing TURP for treatment and diagnosis purposes [8,15]. Our study found that in the past decade, the number of patients diagnosed with TURP had increased yearly; its percentage was supposed to be more than 10%.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, direct TURP for diagnostic purposes is not recommended in patients with suspected PC who have not been screened by biopsy [1,4]. Although it was not recommended, our results, actual clinical practice, and literature report all found that many suspected PC patients were still directly undergoing TURP for treatment and diagnosis purposes [8,15]. Our study found that in the past decade, the number of patients diagnosed with TURP had increased yearly; its percentage was supposed to be more than 10%.…”
Section: Discussionmentioning
confidence: 60%
“…There are very few reports on survival outcomes of TURP-diagnosed PC. This question was answered in a recent retrospective Danish study; they included 64,059 patients with TURP, 63,781 with a final diagnosis of PC, 42,558 of whom were not screened for biopsy; they found that these patients with TPC had a shallow risk of prostate cancer-specific mortality (CSM), the 15-year cumulative incidence was 1.4% for all patients and 0.8% for patients with prostate-specific antigen (PSA) levels <10 ng/mL [8]. While their study only analyzed the survival rates of patients with a PSA of 25ng/mL and below; they also did not analyze the interval between the time of TURP and the time of diagnosis of PC, as well as did not separately analyze the prognosis of patients who underwent TURP without biopsy screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer is the most prevalent noncutaneous malignancy, and it is also the second leading cause of cancer death in males [ 1 ]. Even in men with a benign initial TURP (transurethral resection of the prostate), the 10-year accumulated incidence of prostate cancer was 4.0% [ 2 , 3 ]. In Taiwan, with the increasing use of prostate-specific antigen (PSA) screening, the incidence of prostate cancer has increased over the past decades [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer remains one of the leading causes of death in the US, claiming nearly 600,000 lives each year [ 1 ]. Globally, cancer accounts for almost 16% of all deaths [ 2 ]. Current treatments for cancer, such as chemotherapy, radiation therapy, and surgery, have significant physical and mental effects on the patient [ 3 ].…”
Section: Introductionmentioning
confidence: 99%